(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The monthly fluctuations of Aceria sheldoni population were studied on different citrus varieties at Eleonas in the Aegeon area. Growth cycles of the trees and the seasonal climatic conditions affecting population size. The periods of highest contraction of the population inside the buds and of dispersal are determined as well as the appropriate time to check the growth of the population by intervention. Predator mites, including Phytoseiidae seem little effective in controlling A. sheldoni.